Effect of dietary zinc supplementation on the gastrointestinal microbiome and host gene expression in the Shank3B−/− mouse model of autism spectrum disorder - Wong, Giselle C.; Jung, Yewon; Lee, Kevin; Fourie, Chantelle; Handley, Kim M.; Montgomery, Johanna M.; Taylor, Michael W. (Frontiers in Microbiology, 2025)
Shank gene variants are implicated in ~1% of people with autism, and mice lacking Shank3 exhibit autism-like behaviours. Zinc deficiency and gastrointestinal problems can be common among people with autism, and zinc is a key element required for SHANK protein function and gut development. In Shank3B−/− mice, a supplementary zinc diet reverses autism-like behaviours. We hypothesise that dietary zinc may alter the gut microbiome, potentially affecting the gut-microbiome-brain axis, which may contribute to changes in autism-like behaviours. To test this, four types of gastrointestinal samples (ileum, caecum, colon, faecal) were collected from Shank3B−/− wild-type and knock-out mice on either control or supplemented-zinc diets, enabling us to examine the influence of—and interactions between—dietary zinc, the gut microbiome, and ASD-linked host genotype. Cage, genotype, and zinc diet each contributed significantly to bacterial community variation (accounting for 12.8, 3.9, and 2.3% of the variation, respectively). Fungal diversity was significantly lower in Shank3B−/− compared with wild-type mice on the control zinc diet, with specific fungal biota signatures detected among gut locations. Host metabolic genes, which may be regulated by the gut microbiota, and host genes involved in antimicrobial interactions were more highly expressed in Shank3B−/− mice. Metagenomic analyses revealed differential abundance of bacterial fatty acid biosynthesis and transporters (including zinc transport and neurotransmitter receptors) among our experimental groups. Overall these suggested increased activity of, or a switch towards, metabolic and microbial-host interactions that may benefit both host and microbe, in the presence of zinc. This raises the potential of manipulating both dietary zinc and the gut microbiota itself to ameliorate ASD-related behaviours and associated gastrointestinal issues. These data broaden understanding of the gut microbiome in autism and pave the way towards potential microbial therapeutics for gastrointestinal problems in people with autism.